The right to know the truth in transitional justice processes : perspectives from international law and European governance - Stamenkovikj, Natasha, 1987- (International criminal law series (Leiden, Netherlands), 2021)
"Dr. Natasha Stamenkovikj offers a comparative analysis of the scope and application of the right to the truth as a fundamental right in public international law, and as a concept in European policies for promoting peace and transitional justice. The book provides a systematized assessment of the conceptualisation of the right to the truth in the enlargement policy of the Council of Europe as applied towards the former Yugoslav societies. By assessing the coherence of the Council's standardization on the right to the truth, Dr. Stamenkovikj addresses the legitimacy of the Council as an exporter of values and creator of norms"--